Interhemispheric Approaches to Arteriovenous Malformations: 3-Dimensional Operative Video. Issue 5 (7th August 2018) - Agarwal, Vijay; Barrow, Daniel L
Abstract: We present 2 illustrative cases of interhemispheric approaches to right sided arteriovenous malformations (AVMs). The first patient is a healthy 54-yr-old female who presented with left-sided hearing loss and pulsatile tinnitus, and was neurologically intact. Imaging demonstrated a right sided interhemispheric AVM, fed by the anterior cerebral artery with superficial venous drainage to the superior sagittal sinus. The AVM was thought to be asymptomatic and the patient chose to have her AVM treated surgically to eliminate future risk of hemorrhage. We elected to approach this lesion via a contralateral interhemispheric approach to avoid retraction of the right hemisphere. Intraoperative angiogram demonstrated complete obliteration of the malformation and the patient was neurologically intact postoperatively. The second patient is a 41-yr-old healthy male who presented with progressive bifrontal headaches and was also neurologically intact. Imaging revealed a right interhemispheric AVM fed by the anterior cerebral artery and with superficial venous drainage to the superior sagittal sinus. Although the patient's headaches may have been related, the patient's decision to undergo surgical resection was primarily to eliminate future risk of hemorrhage. The difference with this patient was that imaging revealed the presence of two draining veins on the left side that would potentially be injured via a contralateral approach. As a result, we elected to approach this lesion ipsilaterally. Intraoperative angiogram showed complete obliteration of the malformation with intact venous drainage, and the patient was neurologically intact postoperatively. Contralateral vs ipsilateral interhemispheric approaches are compared and contrasted.